Enhanced Angiogenesis by 11βHSD1 Blockage Is Insufficient to Improve Reperfusion Following Hindlimb Ischaemia - Wu, Junxi; Miller, Eileen; Davidson, Callam; Walker, Brian R.; Hadoke, Patrick W. F. (Frontiers in Cardiovascular Medicine, 2022)
Background: Critical limb ischaemia (CLI), which is estimated to affect 2 million people in the United States, reduces quality of life, is associated with high morbidity and mortality, and has limited treatment options. Direct stimulation of angiogenesis using proangiogenic growth factors has been investigated as a therapeutic strategy to improve reperfusion in the ischaemic leg. Despite positive outcomes in animal studies, there has been little success in clinical translation. This investigation addressed the hypothesis that angiogenesis could be stimulated indirectly in the ischaemic hindlimb by blocking 11β-hydroxysteroid dehydrogenase 1 (11βHSD1)-mediated reactivation of anti-angiogenic glucocorticoids. Method and results: Corticosterone suppressed ex vivo angiogenesis in the mouse aortic ring assay. 11βHSD1 deletion (Hsd11b1Del1/Del1) or pharmacological inhibition (with 300 nM UE2316) which block the reactivation of glucocorticoid (i.e. the conversion of 11-dehydrocorticosterone (11DHC) to bioactive corticosterone) significantly reduced 11DHC-induced suppression of angiogenesis. In a sponge implantation model, 11βHSD1 deletion, but not pharmacological inhibition, enhanced inflammation-induced angiogenesis. By contrast, in the mouse hindlimb ischaemia model, post-ischaemic reperfusion and vascular density were not affected by either deletion or pharmacological inhibition of 11βHSD1 in young or aged mice. 3D vascular imaging suggested that hind limb reperfusion in the first week following induction of ischaemia may be driven by the rapid expansion of collateral arteries rather than by angiogenesis. Conclusion: 11βHSD1-mediated glucocorticoid reactivation suppressed angiogenesis ex vivo and in vivo. However, regulation of angiogenesis alone was insufficient to promote reperfusion in hindlimb ischaemia. Future investigation of post-ischaemic reperfusion should include other aspects of systemic vascular remodelling including arteriogenesis and collateral formation.